Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1979
DOI: 10.1002/app.1979.070240421
|View full text |Cite
|
Sign up to set email alerts
|

Swelling properties of urethane elastomers and their bearing on microphase separation

Abstract: SynopsisSeveral polyurethanes were prepared from polyethylene adipate glycol, 4,4'-diphenylmethane diisocyanate, 1.4-butanedio1, and 3,3'-dichloro-4,4'-diaminodiphenylmethane. The temperature dependence of swelling and dynamic mechanical properties were determined. Analysis of the data shows that microphase separation leaves its mark on the swelling properties and that some information on the extent and perfection of microphase separation can be obtained from swelling. The conclusions were found to be in gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…This way, the coherent scattering signal increased by one order of magnitude and allowed the use of accurate model fitting to reveal details of the microphase morphology. The early work by Nierzwick et al [ 25 ] proved that microphase separation influences the swelling properties of the material, and some information on the extent of microphase separation can be obtained from measuring the swelling ratio. When swelling is done with selective solvents, such as toluene, the hard domains are resistant to the solvent, and the domain structure can remain, though deformed, even in the swollen state.…”
Section: Discussionmentioning
confidence: 99%
“…This way, the coherent scattering signal increased by one order of magnitude and allowed the use of accurate model fitting to reveal details of the microphase morphology. The early work by Nierzwick et al [ 25 ] proved that microphase separation influences the swelling properties of the material, and some information on the extent of microphase separation can be obtained from measuring the swelling ratio. When swelling is done with selective solvents, such as toluene, the hard domains are resistant to the solvent, and the domain structure can remain, though deformed, even in the swollen state.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of phase separation has been raised repeatedly as important to properties of segmented polyurethanes: domain composition is interrelated with the domain structure, and therefore, it is essential to understanding the material mechanical properties. Consequently, considerable effort has gone into characterizing the extent of phase separation. ,,, Information on the domain compositions also is useful to determine the thermodynamic parameters that drive equilibrium phase segregation. Overall, this type of information will provide a basis for predicting the performance of multiphase polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The principal strength of SANS is the increased scattering that can be manipulated by isotopic substitution of deuterium for hydrogen. The combination of swelling and scattering from contrast variation experiments has a sound fundamental basis since solvent swelling experiments have been commonly used in polymer physics for assessing the thermodynamics of mixing and characterization of polymer networks, including those of polyurethanes. , In addition, the analysis of data using contrast variation techniques is well understood. Early work by Nierzwick and Majewska pointed out that such studies could even give information on polyurethane domain composition …”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested the small aggregates may be made up of hard segments originating from the diminished larger hard segment domains. Nierzwicki and Majewska34 determined that the degree of swelling of MDI/BD/PEA [PEA, poly(ethylene adipate) diol, molecular weight, 2000] films by various solvents is affected by the degree of microphase separation. Cooper reported the solvation of the soft and hard segments of a polyester urethane (Estane 5740‐100) by various concentrations of benzene–methanol mixtures 25.…”
Section: Introductionmentioning
confidence: 99%